How Religious Beliefs and Practices Influence the Psychological Health of Catholic Priests. (July 2016) - Isacco, Anthony; Sahker, Ethan; Krinock, Elizabeth; Sim, Wonjin; Hamilton, Deanna
Roman Catholic diocesan priests are a subgroup of men with unique religious and spiritual roles, beliefs, and practices. This qualitative study of 15 priests from the mid-Atlantic area of the United States focused on how priests' relationship with God and promises of celibacy and obedience influenced their psychological health. Using a consensual qualitative research (CQR) design, the analysis revealed that participants described their relationship with God as central to their health and contributing to positive outcomes (e.g., sense of connection and support). The influence of their promises of celibacy and obedience were linked to both positive outcomes (e.g., decreased stress, improved relationships) and negative outcomes (e.g., internal conflict, depression/loneliness). This study highlighted the central role that priests' relationship with God has on positive psychological health. Future research is necessary to understand how to maximize the positive effects and minimize the negative effects of priests' promises of celibacy and obedience, which would benefit programs aimed at supporting priests' psychological health.